Kakintalan mga mabilisang impresyon ng ilang kabataan at gurong Bulakeño - De Veyra, Vicente Ignacio Soria (Bocaue Arts & Cultural Society, 2006)
A collection of literary works by the Bocaue Arts and Cultural Society.